Al Quran and Hadits as Ideas and Sources of Stories in Ahmad Tohari’s Novels - Abdul Wachid Bambang Suharto (IBDA` : Jurnal Kajian Islam dan Budaya, 2022)
The focus of this study is to reveal the religious dimension as a story and the Qur’an and Hadith as ideas and sources of stories in Ahmad Tohari’s works. The method used in this study is a descriptive interpretive method. Data were collected through literature study, interviews, and observations. Data analysis was carried out using qualitative content analysis techniques. The result is that Ahmad Tohari’s works are a sublimation of religious values ​​derived from the Qur’an and Hadith. Ahmad Tohari uses the two sources of Islamic law as a source of stories. Thus, although Ahmad Tohari’s works are known as literary works of human value, they contain religious values ​​or religiosity. Many short stories and novels have raised issues about the economic and social life of the community or the marginalized. However, the work is a literary work that has conditions with religious and prophetic values ​​originating from the Qur’an and Hadith and makes religion a story.